Analysis of student learning outcomes through the task learning approach toward cash pattern construction course - Hadiastuti, Hadiastuti; Ernawati, Ernawati; Suci, Puji Hujria (Universitas Negeri Padang, 2024)
The academic success of students can be measured by their aptitude for classroom learning, the role of lecturer as motivator facilitator, and fulfils other responsibilities in the learning process of a specific unit of competency or subject. The teaching presentation of the fashion pattern construction course incorporated many instructional techniques, including lectures, interactive Q&A sessions, practical exercises, and assignments. Such learning should be cultivated to ascertain the cognitive abilities of pupils in comprehending and effectively applying information to attain favourable learning outcomes. One of the techniques that lecturers can utilize to improve student learning outcomes in the Fashion Pattern Construction course is by adopting the Task Learning approach, because this approach incorporates activities for the benefit of students that can raise their interest and interaction in the course, enhance their engagement and participation in the classroom. So, this study aimed at increasing students’ learning outcomes through task learning approach. The employed approach is classroom action research, comprising four distinct stages: planning, activity, observation, and reflection. A total of 34 students, all of whom were D3 fashion design students, were the subjects of this study. The findings demonstrated the efficacy of the Task Learning methodology in enhancing student learning outcomes, as seen by the percentage increase in student learning outcomes observed between cycle 1 and cycle 2.